Trade, Land, Power : The Struggle for Eastern North America - Richter, Daniel K. (Book collections on Project MUSE., 2013)
In this collection of essays, a colonial historians reexamines struggles between Native peoples and Europeans in early America in terms of how each understood the material basis of power.